2018
DOI: 10.1002/slct.201703036
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbic Acid as a Highly Efficient Organocatalyst for ipso‐Hydroxylation of Arylboronic Acid

Abstract: An effective organocatalyst, ascorbic acid has been successfully applied for the ipso-hydroxylation of arylboronic acid using 30% aqueous H 2 O 2 as oxidant in water at ambient temperature. The methodology proceeds without using any metal catalyst or base and avoids harsh reaction conditions. The protocol is applicable to various electronically diverse arylboronic acid moieties with good to excellent yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…In particular, during recent times aerial oxygen mediated approaches towards the synthesis of phenolic derivatives have found greater value in synthetic organic chemistry. These methods are using benzoquinone, gallic acid, ascorbic acid and rose bengal as organocatalysts for the ipso ‐hydroxylation of boronic acids. Also, it was reported that the aerial oxygen can be introduced as an oxidant to accomplish the desired chemical transformations .…”
Section: Methodsmentioning
confidence: 99%
“…In particular, during recent times aerial oxygen mediated approaches towards the synthesis of phenolic derivatives have found greater value in synthetic organic chemistry. These methods are using benzoquinone, gallic acid, ascorbic acid and rose bengal as organocatalysts for the ipso ‐hydroxylation of boronic acids. Also, it was reported that the aerial oxygen can be introduced as an oxidant to accomplish the desired chemical transformations .…”
Section: Methodsmentioning
confidence: 99%
“…Still, the methodology took a longer reaction time, and a low yield of the desired product was obtained [19] . Sequentially, further advancement in the catalytic system has been progressed, and a wide array of the non‐metallic catalytic system has been developed, which utilized WERSA‐H 2 O 2 , [25] ascorbic acid‐H 2 O 2 , [26] TBHP‐KOH, [20] and N ‐oxide [23] . Recently, He group reported microwave‐assisted aerobic hydroxylation of boronic acid using KOH and DMSO [27] .…”
Section: Figurementioning
confidence: 99%
“…The catalytic system was proved to be effective even after five cycles without significant loss of activity. Recently, the same group reported that ascorbic acid could act as a highly efficient organocatalyst for the hydroxylation of aryl boronic acids (Scheme a) …”
Section: Thermal Catalytic Conversion Of Aryl Boronic Compounds Tomentioning
confidence: 99%